Silica gel dehumidification material as well as preparation method and application thereof

By using specific modifiers and multiple modification treatments in silica gel dehumidification materials, the problems of insufficient hygroscopic ability and short service life in high humidity environments are solved, and higher hygroscopic properties and structural stability are achieved.

CN119680511APending Publication Date: 2025-03-25JIANGSU SUJING GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887578.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicone dehumidifier materials lack moisture absorption capacity in high humidity environments, and their service life is short after modification, and their moisture absorption performance will significantly decrease during recycling.

Method used

The silica gel is pretreated with specific modifiers such as alkali metal acetate and/or alkali metal acetate phosphate to form a stable ion exchange layer, and then multiple modifications are performed using aqueous magnesium chloride solution and calcium chloride solution to enhance hygroscopic properties and structural stability.

Benefits of technology

It significantly improves the moisture absorption performance and structural stability of silicone dehumidification materials, extends the circulation life, reduces the risk of matrix fracture, and achieves better comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005202893250000091
    Figure BDA0005202893250000091
  • Figure BDA0005202893250000092
    Figure BDA0005202893250000092
  • Figure BDA0005202893250000093
    Figure BDA0005202893250000093
Patent Text Reader

Abstract

The invention discloses a silica gel dehumidification material and a preparation method and application thereof, and the preparation method comprises the following steps: dispersing silica gel particles and a modifier in water to prepare a silica gel dispersion liquid; the modifier comprises alkali metal acetate and / or alkali metal dihydrogen phosphate; the preparation method comprises the following steps: dipping a matrix material in a silica gel dispersion liquid, taking out and drying to obtain a first silica gel dehumidification material intermediate, dipping the first silica gel dehumidification material intermediate in a magnesium chloride aqueous solution, taking out and drying to obtain a second silica gel dehumidification material intermediate, dipping the second silica gel dehumidification material intermediate in a calcium chloride alcoholic solution, taking out and drying to obtain the silica gel dehumidification material, the silica gel dehumidification material prepared by the method has high moisture absorption performance and long cycle service life, and can be applied to preparation of dehumidification products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas dehumidification, and in particular to a silica gel dehumidification material and a preparation method and application thereof. Background Art

[0002] In the field of materials science and engineering, with the growing demand for industrial production and environmental protection, the research and development of efficient dehumidification materials has become a focus of attention. Traditional silica gel dehumidification materials have shown unique advantages in many applications due to their good adsorption performance and chemical stability, especially in air drying and gas purification. In recent years, the hygroscopic capacity and service life of silica gel have been further improved by chemical modification, so that it can still maintain efficient hygroscopic performance under changing working conditions. However, although these advances have significantly improved the performance of silica gel dehumidification materials, there are still some challenges. For example, the water absorption rate of ordinary silica gel is not high, especially in high humidity environments, its hygroscopic capacity still needs to be improved. In addition, although there are some modifications to silica gel to improve its hygroscopic performance, the modified silica gel material has a short service life, and the hygroscopic performance will decrease significantly after a limited period of use. Summary of the invention

[0003] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide a method for preparing an improved silica gel dehumidification material. The silica gel dehumidification material prepared by the method can simultaneously have high moisture absorption performance and cycle life.

[0004] The present invention also provides an application of the silica gel dehumidification material in the preparation of dehumidification products, and the dehumidification products include but are not limited to dehumidification wheels, layered dehumidification products, and the like.

[0005] In order to achieve the above object, a technical solution adopted by the present invention is:

[0006] A method for preparing a silica gel dehumidification material, the preparation method comprising:

[0007] (i) dispersing silica gel particles and a modifier in water to prepare a silica gel dispersion; the modifier comprises an alkali metal acetate and / or an alkali metal dihydrogen phosphate;

[0008] (ii) immersing the matrix material in the silica gel dispersion, taking it out and drying it to obtain a first silica gel dehumidification material intermediate;

[0009] (iii) immersing the first silica gel dehumidification material intermediate in a magnesium chloride aqueous solution, taking it out and drying it to obtain a second silica gel dehumidification material intermediate;

[0010] (iv) The second silica gel dehumidification material intermediate is immersed in a calcium chloride alcohol solution, taken out and dried to obtain a silica gel dehumidification material.

[0011] According to some preferred aspects of the present invention, in step (i), the mass ratio of the silica gel particles to the modifier is 1:1-4.

[0012] In some preferred embodiments of the present invention, in step (i), the modifier is a combination of one or more selected from sodium acetate, potassium acetate, sodium dihydrogen phosphate and potassium dihydrogen phosphate.

[0013] According to some preferred aspects of the present invention, in step (i), the silica gel particles are pretreated before use by drying the silica gel particles at 105-120°C to remove physically adsorbed water on the surface and to remove gas from the silica gel pores to obtain pretreated silica gel particles.

[0014] According to some specific aspects of the present invention, in step (i), the silica gel particles are a combination of one or more selected from macroporous silica gel, coarse pore silica gel, type B silica gel and fine pore silica gel.

[0015] Furthermore, macroporous silica gel is silica gel with a pore size greater than 50nm and a specific surface area of ​​100-300㎡ / g; coarse-pore silica gel is silica gel with a pore size between 30nm and 50nm and a specific surface area of ​​300-600㎡ / g; type B silica gel is silica gel with a pore size between 15nm and 30nm and a specific surface area of ​​400-600㎡ / g; fine-pore silica gel is silica gel with a pore size less than 15nm and a specific surface area of ​​600-1000㎡ / g.

[0016] In some preferred embodiments of the present invention, in step (ii), the substrate material is composed of one or more of ceramic fibers, natural fibers and synthetic fibers.

[0017] In some preferred embodiments of the present invention, the mass concentration of the silica gel dispersion is controlled to be 15%-40%.

[0018] In some preferred embodiments of the present invention, during the process of preparing the silica gel dispersion, magnetic stirring is used for stirring.

[0019] According to some preferred aspects of the present invention, in step (iii), the mass concentration of the magnesium chloride aqueous solution is 10%-50%, further 20%-30%.

[0020] In some embodiments of the present invention, magnesium chloride solid and water are weighed in a mass ratio of 2:8 to 3:7, the magnesium chloride solid is added to the water, and stirred until the magnesium chloride solid is completely dissolved to obtain the magnesium chloride aqueous solution.

[0021] According to some preferred aspects of the present invention, in step (iii), the immersion time is controlled to be 10-60 h, further 20-55 h, and further 30-55 h.

[0022] According to some preferred aspects of the present invention, in step (iv), the calcium chloride alcohol solution is an anhydrous ethanol solution of calcium chloride.

[0023] According to some preferred aspects of the present invention, in step (iv), the mass concentration of the calcium chloride alcohol solution is 10%-35%, further 15%-25%.

[0024] In some embodiments of the present invention, calcium chloride solid and anhydrous ethanol are weighed in a mass ratio of 3:17 to 5:15, the calcium chloride solid is added to the anhydrous ethanol, and stirred until the calcium chloride solid is completely dissolved to obtain the calcium chloride alcohol solution.

[0025] According to some preferred aspects of the present invention, in step (iv), the immersion time is controlled to be 10-60 hours, further 20-55 hours, and further 30-55 hours.

[0026] According to some preferred aspects of the present invention, the mass ratio of the silica gel particles, the magnesium chloride and the calcium chloride is 1:6-14:5-10, further 1:8-12:7-8.

[0027] Another technical solution provided by the present invention is a silica gel dehumidification material made by the preparation method of the silica gel dehumidification material described above.

[0028] Another technical solution provided by the present invention is: an application of the silica gel dehumidification material described above in the preparation of dehumidification products.

[0029] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0030] Based on the problem that the existing modified silica gel dehumidification materials have insufficient dehumidification performance and a short service life after modification, the inventors of the present invention have found in a large number of experimental studies that the silica gel material is unexpectedly damaged during the modification process, making its structure unstable and prone to matrix rupture during recycling, which in turn causes irreversible damage to the silica gel dehumidification material during moisture absorption and regeneration, resulting in a decrease in moisture absorption performance.

[0031] Based on this, the present invention innovatively proposes to pre-treat silica gel with specific modifiers (such as alkali metal acetate and / or alkali metal dihydrogen phosphate), which can form a relatively stable ion exchange layer with the hydroxyl groups on the surface of silica gel to achieve modification and protection of the surface of silica gel, and then use magnesium chloride aqueous solution for the second modification and calcium chloride alcohol solution for the third modification, wherein magnesium chloride has high solubility and reactivity in aqueous solution, so that it can efficiently bond with the hydroxyl groups on the surface of silica gel to form a stable magnesium oxygen bond, while enhancing the hygroscopic performance of silica gel, improving structural stability and reducing the risk of matrix rupture; in addition, through aqueous solution modification, it can ensure that magnesium chloride molecules fully penetrate into the micropores and mesopores of silica gel to form a uniform modified layer; the use of calcium chloride alcohol solution for modification can absorb chlorine through physical adsorption or weak hydrogen bonding. Calcium chloride gradually penetrates into the pores of silica gel. By using an aqueous solution first and then an alcohol solution, the limitations of a single modifier are avoided, the best hygroscopic performance and structural stability are achieved, and the risk of matrix rupture is reduced. Furthermore, magnesium chloride forms a strong bond with the hydroxyl groups on the surface of silica gel through hydration, occupying most of the adsorption sites, so that the calcium chloride molecules interact with silica gel mainly through physical adsorption or weak hydrogen bonding. Therefore, although the alcohol molecules compete with the calcium chloride molecules for some adsorption sites, they will not significantly affect the modification effect of calcium chloride. When modified with calcium chloride alcohol solution, the calcium chloride molecules can gradually penetrate into the pores of silica gel through physical adsorption or weak hydrogen bonding. In addition, the presence of alcohol molecules helps to prevent the concentration of calcium chloride molecules from being too high in local areas, thereby optimizing the distribution of calcium chloride in the pores of silica gel and avoiding pore blockage or structural deformation.

[0032] Practice has shown that the silica gel dehumidification material prepared by the method of the present invention can significantly improve the moisture absorption performance and structural stability, improve the regeneration performance, and increase the cycle life. It overcomes the unexpected damage to the silica gel structure caused by the modified silica gel dehumidification material in the prior art, and thus effectively guarantees the structural stability of the dehumidification material, reduces the problem of matrix rupture, and ultimately achieves a silica gel dehumidification material with better comprehensive performance. DETAILED DESCRIPTION

[0033] The present invention aims to provide a silica gel dehumidification material having at least high moisture absorption capacity and high recycling performance and a preparation method thereof.

[0034] This embodiment provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0035] (i) dispersing silica gel particles and a modifier in water to prepare a silica gel dispersion; the modifier comprises an alkali metal acetate and / or an alkali metal dihydrogen phosphate;

[0036] (ii) immersing the matrix material in the silica gel dispersion, taking it out and drying it to obtain a first silica gel dehumidification material intermediate;

[0037] (iii) immersing the first silica gel dehumidification material intermediate in a magnesium chloride aqueous solution, taking it out and drying it to obtain a second silica gel dehumidification material intermediate;

[0038] (iv) The second silica gel dehumidification material intermediate is immersed in a calcium chloride alcohol solution, taken out and dried to obtain a silica gel dehumidification material.

[0039] Furthermore, in step (i), the silica gel particles are placed in a drying oven at a temperature of 105°C to 120°C and dried for 3-6 hours to remove physically adsorbed water on the surface and to remove gas in the silica gel pores to obtain dry silica gel particles; then the dried silica gel particles and the modifier are dispersed in water respectively, and stirred at room temperature for 30-60 minutes to form a slurry mixture, i.e., a silica gel dispersion; wherein the mass ratio of the silica gel particles to the modifier is 1:1-4, the modifier is a combination of one or more selected from sodium acetate, potassium acetate, sodium dihydrogen phosphate and potassium dihydrogen phosphate, and the silica gel particles are a combination of one or more selected from macroporous silica gel, coarse-porous silica gel, type B silica gel and fine-porous silica gel.

[0040] Furthermore, in step (ii), the matrix material is cut into a preset shape, such as a sheet, and is immersed in a slurry mixture, i.e., a silica gel dispersion, for 10-30 minutes and then taken out; the immersed matrix material is placed in a drying oven at a temperature of 105°C to 120°C and dried for 3-6 hours to obtain a first silica gel dehumidification material intermediate.

[0041] Further, in step (iii), the first silica gel dehumidification material intermediate is immersed in the magnesium chloride aqueous solution with a mass concentration of 10%-50%, and after immersion for 36h-48h, it is filtered and placed in a drying oven at 105°C-120°C for 2h-4h to obtain a second silica gel dehumidification material intermediate; since the silica gel is pre-treated with a modifier to form a relatively stable ion exchange layer, the high solubility and reactivity of magnesium chloride in aqueous solution enable it to efficiently chemically bond with the hydroxyl groups on the surface of the silica gel to form a stable magnesium oxygen bond, while enhancing the hygroscopic performance of the silica gel, improving the structural stability and reducing the risk of matrix rupture. In addition, by modifying the aqueous solution, it can be ensured that the magnesium chloride molecules fully penetrate into the micropores and mesopores of the silica gel to form a uniform modified layer.

[0042] Further, in step (iv), the second silica gel dehumidification material intermediate is immersed in an anhydrous ethanol solution of calcium chloride with a mass concentration of 10%-35%, and after immersion for 36h-48h, it is filtered and placed in a drying oven at 65°C-85°C for 1h-4h to obtain a silica gel dehumidification material; magnesium chloride forms a strong chemical bond with the hydroxyl groups on the surface of silica gel through hydration, occupying most of the adsorption sites, so that the calcium chloride molecules interact with the silica gel mainly through physical adsorption or weak hydrogen bonding. Therefore, although the alcohol molecules compete with the calcium chloride molecules for some adsorption sites, they will not significantly affect the modification effect of calcium chloride. Using calcium chloride alcohol solution for modification, the calcium chloride molecules can gradually penetrate into the pores of silica gel through physical adsorption or weak hydrogen bonding. In addition, the presence of alcohol molecules helps to prevent the concentration of calcium chloride molecules from being too high in local areas, thereby optimizing the distribution of calcium chloride in the pores of silica gel and avoiding pore blockage or structural deformation.

[0043] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0044] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0045] Type B silica gel was purchased from Qingdao Haiwan Group Co., Ltd. and the implementation standard was HG / T2765.6-2005.

[0046] Example 1

[0047] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0048] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0049] Add 10 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0050] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0051] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0052] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0053] Example 2

[0054] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0055] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0056] Add 20 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0057] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0058] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0059] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0060] Example 3

[0061] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0062] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0063] Add 30 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0064] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0065] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0066] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0067] Example 4

[0068] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0069] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0070] Add 40 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0071] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0072] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0073] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0074] Example 5

[0075] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0076] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0077] Add 30 g of sodium acetate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0078] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0079] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0080] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0081] Comparative Example 1

[0082] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0083] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0084] Add 100 mL of water to 10 g of type B silica gel after drying, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0085] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0086] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0087] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0088] Comparative Example 2

[0089] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0090] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0091] Add 30 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0092] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0093] Weigh 100 g of magnesium chloride, add 300 mL of water, stir and mix to obtain a magnesium chloride aqueous solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride aqueous solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate;

[0094] Weigh 75g of calcium chloride, add 350mL of water, stir and mix to obtain a calcium chloride aqueous solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride aqueous solution for 48h, filter and dry in a drying oven preheated to 70°C for 2 hours to obtain a silica gel dehumidification material.

[0095] Comparative Example 3

[0096] This example provides a method for preparing a silica gel dehumidification material and the silica gel dehumidification material prepared therefrom, which specifically comprises the following steps:

[0097] Weigh 10 g of type B silica gel, put it into a drying oven preheated to 110°C and dry it for 4 hours to remove the physically adsorbed water on the surface and remove the gas in the silica gel pores, take it out and cool it to room temperature to obtain dry type B silica gel;

[0098] Add 30 g of sodium dihydrogen phosphate to 10 g of type B silica gel after drying, then add 100 mL of water, and stir with a magnetic stirrer at room temperature for 45 min to form a silica gel dispersion;

[0099] The ceramic fiber matrix was cut into square pieces of 50 cm×50 cm, immersed in a silica gel dispersion for 20 minutes, taken out and placed in a drying oven preheated to 110° C. for 4 hours to obtain a first silica gel dehumidification material intermediate;

[0100] Weigh 100 g of magnesium chloride, add 2000 mL of anhydrous ethanol, stir and mix to obtain a magnesium chloride alcohol solution, immerse the first silica gel dehumidification material intermediate in the magnesium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 110° C. for 3 hours to obtain a second silica gel dehumidification material intermediate.

[0101] Weigh 75 g of calcium chloride, add 350 mL of anhydrous ethanol, stir and mix to obtain a calcium chloride alcohol solution, immerse the second silica gel dehumidification material intermediate in the calcium chloride alcohol solution for 48 hours, filter and dry in a drying oven preheated to 70° C. for 2 hours to obtain a silica gel dehumidification material.

[0102] Performance Testing

[0103] Analysis of moisture absorption and regeneration performance:

[0104] The regeneration of silica gel, that is, its ability to restore its moisture absorption capacity during the moisture absorption-desorption cycle, can indirectly reflect its breakage risk by observing its structural integrity and functional stability after multiple cycles. If silica gel frequently suffers structural damage or performance degradation during the regeneration process, such as a significant decrease in moisture absorption, it means that it has broken inside, resulting in damage to the pore structure, which in turn affects its regeneration performance. Therefore, regeneration is an important indicator for assessing the risk of silica gel breakage.

[0105] 1) The silica gel dehumidification materials in Examples 1-5 and Comparative Examples 1-3 were placed in an environment with a temperature of 30°C and a relative humidity of 70% to absorb moisture until no liquid overflowed from the surface of the silica gel dehumidification materials. The moisture absorption time was recorded, and the mass change of the materials before and after moisture absorption was weighed to calculate the moisture absorption amount.

[0106] 2) Place the dehumidified silica gel dehumidification material in a 110°C constant temperature oven for 4 hours to remove the adsorbed moisture. Weigh the mass change before and after drying to calculate the dehumidification amount.

[0107] 3) Repeat steps 1) and 2) for 5 cycles, and record the moisture absorption and desorption each time.

[0108] in:

[0109] Moisture absorption (g) = material mass after moisture absorption (g) - material mass before moisture absorption (g);

[0110] Dehumidification amount (g) = material mass before activation (g) - material mass after activation (g);

[0111] Moisture absorption efficiency (%) = moisture absorption (g) / material mass before moisture absorption (g) * 100%;

[0112] Dehumidification efficiency (%) = dehumidification amount (g) / material mass before activation (g) * 100%.

[0113] The experimental data are shown in Tables 1 to 5:

[0114] Table 1 Example 1-2 Moisture absorption-dehumidification cycle data

[0115]

[0116] Table 2 Example 4-5 moisture absorption-dehumidification cycle data

[0117]

[0118] Table 3 Moisture absorption-dehumidification cycle data of Example 3 and Comparative Example 1

[0119]

[0120] Table 4 Moisture absorption-dehumidification cycle data of comparative example 2 and comparative example 3

[0121]

[0122] Table 5 The ratio of the moisture absorption after 5 cycles of Examples 1-5 and Comparative Examples 1-3

[0123]

[0124] In Example 3 and Comparative Example 1: the initial moisture absorption (35.78g) and the average moisture absorption after the cycle (34.55g) of Example 3 are significantly higher than those of Comparative Example 1 (16.10g and 14.30g, respectively), and the moisture absorption efficiency of Example 3 is higher, the moisture absorption performance decays more slowly, and the moisture absorption decrease ratio is 6.3%, while that of Comparative Example 1 is 22.8%. Analysis shows that this should be due to the fact that the addition of sodium dihydrogen phosphate pretreatment can significantly improve the moisture absorption performance. The sodium dihydrogen phosphate pretreatment forms more active adsorption sites on the surface of the silica gel, enhances the adsorption of water molecules and subsequent modifiers, and stabilizes the surface structure, improving the regeneration ability of the silica gel. However, due to the lack of pretreatment steps in Comparative Example 1, the silica gel surface lacks active sites, resulting in weak adsorption capacity, unstable moisture absorption structure, and faster performance decay during the cycle. Further, it is believed that when sodium dihydrogen phosphate is dissolved in water, dihydrogen phosphate ions and sodium ions are dissociated. When the solution comes into contact with silica gel, the silanol groups on the surface of the silica gel will partially dissociate to produce silicon oxygen anions and hydrogen ions. These hydrogen ions and the sodium ions in the solution will be adsorbed near the silicon oxygen anions due to electrostatic action, forming a charge balance state. The dihydrogen phosphate ions interact with the cations around the silicon oxygen anions through electrostatic action to form an electrostatic attraction; at the same time, the oxygen atoms in the dihydrogen phosphate ions form hydrogen bonds with the hydrogen atoms of the silanol groups, so that the dihydrogen phosphate ions form a stronger interaction with the silica gel surface, so that the hydrogen ions and sodium ions originally adsorbed around the silicon oxygen anions are separated from the silica gel surface due to the weakened attraction; when the originally adsorbed sodium ions are separated, other free sodium ions in the solution quickly diffuse to the silica gel surface to maintain local charge balance. Finally, the dihydrogen phosphate ions form a dynamic adsorption layer on the silica gel surface that is mainly composed of dihydrogen phosphate ions and contains a small amount of sodium ions, thereby achieving the modification of the silica gel surface.

[0125] In Examples 1-4: the effect of the amount of sodium dihydrogen phosphate on the hygroscopic performance of the modified silica gel shows a trend of first increasing and then decreasing: the initial hygroscopic capacity increases with the increase in the amount, reaching a peak value at 30g, and then slightly increasing; the hygroscopic efficiency decreases most slowly at a dosage of 30g during the cycle, showing the best stability, and then slightly decreases; at the same time, the hygroscopic capacity of 30g decreases at the lowest rate after the cycle, and the average hygroscopic capacity is the highest. This is because an appropriate amount of sodium dihydrogen phosphate can effectively modify the surface of silica gel, increase hygroscopic active sites and promote the fixation of the modifier. However, when the amount exceeds 30g, excessive phosphate may accumulate on the surface of silica gel to form a multi-layer coverage, which not only blocks the pores and reduces the specific surface area, but also may cause the modified layer structure to be unstable, thereby reducing the hygroscopic performance and regeneration capacity. Therefore, 30g of sodium dihydrogen phosphate (sodium dihydrogen phosphate to type B silica gel feed ratio of 3:1) is the optimal amount to achieve the best balance between hygroscopic performance and regeneration capacity.

[0126] Example 3 and Example 5: The initial moisture absorption capacity (35.78g), the average moisture absorption capacity after the cycle (34.55g), the moisture absorption efficiency and the moisture absorption capacity reduction ratio after the cycle (6.3%) of Example 3 are significantly better than those of Example 5 (25.76g, 24.09g, and 13.6%, respectively). Analysis shows that this is because the phosphate ions generated by the ionization of sodium dihydrogen phosphate have a stronger electrostatic interaction with the silica gel surface and the subsequent modifier, and are easier to form a stable three-dimensional adsorption layer, which can promote the fixation of metal ions and significantly improve the moisture absorption performance and cycle stability. The modification effect of sodium acetate is relatively weak, and the surface structure formed is not as stable as phosphate, resulting in relatively weak moisture absorption performance and regeneration ability.

[0127] In Example 3, Comparative Example 2 and Comparative Example 3: the initial moisture absorption capacity (35.78g), average moisture absorption capacity (34.55g) and moisture absorption efficiency of Example 3 are significantly higher than those of Comparative Example 2 (32.20g, 29.41g, respectively) and Comparative Example 3 (31.48g, 29.10g, respectively), and the moisture absorption capacity reduction ratio (6.3%) of Example 3 is also significantly lower than that of Comparative Example 2 (16.6%) and Comparative Example 3 (14.5%). Analysis shows that this is because the best moisture absorption performance can be obtained by modifying the magnesium chloride aqueous solution and the calcium chloride alcohol solution in combination. The magnesium chloride aqueous solution can promote the full dissolution and ionization of magnesium ions and make them better adsorbed on the silica gel surface, while the calcium chloride alcohol solution can reduce the influence of calcium ion hydration, allowing the calcium ions to be more evenly dispersed on the silica gel surface to form a uniform modified layer; in contrast, the use of the calcium chloride aqueous solution in Comparative Example 2 causes pore blockage and uneven modification due to excessive hydration, while the use of the magnesium chloride alcohol solution in Comparative Example 3 reduces the hygroscopic performance due to insufficient solubility and competitive adsorption.

[0128] Further, it can be seen from Example 3 compared with Comparative Examples 2-3 that if only aqueous solution is used for modification, the risk of matrix rupture will increase, especially under high humidity environment. In addition, the modifier molecules in the aqueous solution are easily crystallized during high temperature drying, which will affect the pore structure and hygroscopic properties of silica gel. Similarly, if only alcohol solution is used for modification, because the solubility of the modifier in alcohol is low, the modification effect is not thorough, and the hygroscopic performance is limited. In addition, the competitive effect of alcohol molecules may also weaken the reaction efficiency of the modifier and the silica gel surface, further affecting the modification effect. The present invention first uses magnesium chloride aqueous solution for modification, and then uses calcium chloride alcohol solution for modification, which can effectively avoid the above problems. Magnesium chloride aqueous solution can efficiently chemically bond with the silica gel surface, enhance its hygroscopic properties and structural stability, and reduce the risk of matrix rupture. Calcium chloride alcohol solution can further optimize the pore structure and reduce the risk of matrix rupture under the premise of maintaining structural stability, and finally prepare a composite modified silica gel dehumidification material with better performance. By using an aqueous solution first and then an alcohol solution, the limitations of a single modifier can be avoided and optimal hygroscopic performance and structural stability can be achieved.

[0129] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0130] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a silica gel dehumidification material, characterized in that: The preparation method comprises: (i) dispersing silica gel particles and a modifier in water to prepare a silica gel dispersion; the modifier comprises an alkali metal acetate and / or an alkali metal dihydrogen phosphate; (ii) immersing the matrix material in the silica gel dispersion, taking it out and drying it to obtain a first silica gel dehumidification material intermediate; (iii) immersing the first silica gel dehumidification material intermediate in a magnesium chloride aqueous solution, taking it out and drying it to obtain a second silica gel dehumidification material intermediate; (iv) The second silica gel dehumidification material intermediate is immersed in a calcium chloride alcohol solution, taken out and dried to obtain a silica gel dehumidification material.

2. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (i), the mass ratio of the silica gel particles to the modifier is 1:1-4.

3. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (i), the modifier is a combination of one or more selected from sodium acetate, potassium acetate, sodium dihydrogen phosphate and potassium dihydrogen phosphate.

4. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (i), the silica gel particles are pretreated before use, and the silica gel particles are placed at 105-120°C for drying to remove physically adsorbed water on the surface and to remove gas in the silica gel pores to obtain pretreated silica gel particles; and / or, in step (i), the silica gel particles are a combination of one or more selected from macroporous silica gel, coarse-porous silica gel, type B silica gel and fine-porous silica gel.

5. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (ii), the substrate material is composed of one or more of ceramic fibers, natural fibers and synthetic fibers; and / or the mass concentration of the silica gel dispersion is controlled to be 15%-40%.

6. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (iii), the mass concentration of the magnesium chloride aqueous solution is 10%-50%, further 20%-30%; and / or, in step (iii), the immersion time is controlled to be 10-60h, further 20-55h, further 30-55h.

7. The method for preparing the silica gel dehumidification material according to claim 1, characterized in that: In step (iv), the calcium chloride alcohol solution is an anhydrous ethanol solution of calcium chloride; and / or, in step (iv), the mass concentration of the calcium chloride alcohol solution is 10%-35%, further 15%-25%; and / or, in step (iv), the immersion time is controlled to be 10-60h, further 20-55h, and further 30-55h.

8. The method for preparing a silica gel dehumidification material according to claim 1, characterized in that: The mass ratio of the silica gel particles, the magnesium chloride and the calcium chloride is 1:6-14:5-10, and further 1:8-12:7-8.

9. A silica gel dehumidification material made according to the preparation method of silica gel dehumidification material according to any one of claims 1 to 8.

10. Use of the silica gel dehumidification material according to claim 9 in preparing dehumidification products.